2018
DOI: 10.3389/fnins.2017.00735
|View full text |Cite
|
Sign up to set email alerts
|

Does Otovestibular Loss in the Autosomal Dominant Disorder DFNA9 Have an Impact of on Cognition? A Systematic Review

Abstract: Background and Purpose: Cognitive impairment has been observed in patients with bilateral vestibular loss (BVL) and in patients with sensorineural hearing loss (SNHL). DFNA9 is an autosomal dominant disorder that causes a combination of both sensory deficits by the 3rd to 5th decade. We therefore hypothesize a combined detrimental effect on cognition. The aim of this systematic review was to identify studies related to DFNA9 in general and its relationship with cognitive impairment more specifically.Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Afterwards, the pressure difference drops (pressures in both scalae are high) and a loss of input pressure drive occurs, finally causing sensorineural hearing loss (17). Van Rompaey et al already suggested a correlation between these described fibrous tissue deposits and vestibular function loss (18,19). Their study in patients with bilateral severe-to-profound SNHL, eligible for cochlear implantation, but excluding DFNA9 patients, showed abnormalities on T2-weighted MRI correlating to caloric areflexia.…”
Section: Discussionmentioning
confidence: 98%
“…Afterwards, the pressure difference drops (pressures in both scalae are high) and a loss of input pressure drive occurs, finally causing sensorineural hearing loss (17). Van Rompaey et al already suggested a correlation between these described fibrous tissue deposits and vestibular function loss (18,19). Their study in patients with bilateral severe-to-profound SNHL, eligible for cochlear implantation, but excluding DFNA9 patients, showed abnormalities on T2-weighted MRI correlating to caloric areflexia.…”
Section: Discussionmentioning
confidence: 98%
“…The most frequent reported etiologies of BV are ototoxic (aminoglycosides antibiotics), Menière's disease and infections [2][3][4]. In Belgium and the Netherlands a relative higher proportion of genetic etiology is found due to a COCH mutation causing DFNA9 disease, which is the most common type of autosomal dominant non-syndromic deafness [5]. However, in about half of all BV patients no underlying etiology can be identified that caused their vestibular loss [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its close relationship to the cochlea, the vestibular system has also been implicated in cognitive decline (27). However, because earlier studies did not take a potentially concomitant sensorineural hearing loss in to account or were performed in a static condition, further research will be necessary to identify its role (28)(29)(30)(31)(32).…”
Section: Hearing Loss and Cognitive Decline Are Linkedmentioning
confidence: 99%
“…However, the results of studies investigating the effect of hearing aids on cognitive function in older adults are inconclusive (40)(41)(42)(43)(44)(45)(46)(47). Recent studies have also studied the impact of unilateral cochlear implantation on the cognitive capabilities of older adults with bilateral severe-to-profound sensorineural hearing loss (28,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). While cochlear implantation leads to a significant improvement of speech understanding in older adults and some improvement in cognition overall when compared to the preoperative performance, even experienced cochlear implant users still underperform when compared with their peers when matched for age, sex and education.…”
Section: Can Hearing Rehabilitation Slow Down Cognitive Decline?mentioning
confidence: 99%
See 1 more Smart Citation